Simultaneous determination of ten neonicotinoid insecticides and two metabolites in honey and Royal-jelly by solid−phase extraction and liquid chromatography−tandem mass spectrometry. (1st January 2019) - Hou, Jianbo; Xie, Wen; Hong, Deng; Zhang, Wenhua; Li, Fei; Qian, Yan; Han, Chao
Highlights: This article describe multiresidue analysis of neonicotinoid insecticides in honey and royal-jelly samples. This article is the first paper in this field. A LC–MS/MS method was developed and optimized. The detailed interpretation of the target analytes MS fragmentation was first provided. Abstract: An analytical method based on liquid chromatography-tandem mass spectrometry (LC–MS/MS) method was developed for the first simultaneous determination of ten neonicotinoid insecticides (pymetrozine, dinotefuran, nitenpyram, thiamethoxam, flonicamid, imidacloprid, clothianidin, imidaclothiz, acetamiprid, thiacloprid) and two metabolites (4-trifluoromethylnicotinamide and N-desmethylacetamiprid) in honey and royal-jelly. The quantitative detection was performed by LC–MS/MS on multiple reaction monitoring (MRM) mode under positive-ion electrospray ionization. The isotope dilution internal standard method or external standard method was used for quantitation analysis. The limits of quantification (LOQs), calculated as 10 times the standard deviation, were 0.25–5.0 µg kg −1 for ten neonicotinoid insecticides and two metabolites. The average recoveries were in the range of 72.8–106.5%, with relative standard deviations (RSDs) below 13.8%, measured at three concentration levels. The developed method exhibits a high sensitivity and suitable for the simultaneous determination of neonicotinoid insecticides and metabolites in honey and royal-jelly.